Karekteristik Tujuan Anggaran Terhadap Kinerja Aparat Pemerintah Daerah pada Organisasi Perangkat Daerah - Victor Pattiasina; Muhamad Yamin Noch; Andarias Patiran; Melyanus Bonsapia (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2020)
This research is the criteria concerning the influence of the characteristics of budget objectives on the performance of localgovernment officials in the Keerom regency regional apparatus organization. Testing was carried out on a sample of 73respondents. The sample method used was Porpusive sampling. Data collection was carried out by direct survey. Testing testing is tested empirically using multiple regression. The results showed that budget preparation had a positive and insignificant effect on the performance of local government officials in Keerom Regency. Budget feedback did not have a positive and significant effect on the performance of local government officials in Keerom Regency, local governments evaluated that the budget had no positive and significant effect on the performance of local government officials in Keerom Regency. , Clarity of budget targets has a positive and significant effect on the performance of local government officials in Keerom Regency. The difficulty of budget objectives has a positive and significant effect on the performance of local government officials in Keerom Regency and participation in budget formulation, budget evaluation, clarity of budget targets and difficulty of simultaneous budget objectives on the performance of government officials. Keerom Regency area.